Identification of a Functional Susceptibility Variant for Adolescent Idiopathic Scoliosis that Upregulates Early Growth Response 1 (EGR1)‐Mediated UNCX Expression. (23rd November 2022) - Yonezawa, Yoshiro; Guo, Long; Kakinuma, Hisaya; Otomo, Nao; Yoshino, Soichiro; Takeda, Kazuki; Nakajima, Masahiro; Shiraki, Toshiyuki; Ogura, Yoji; Takahashi, Yohei; Koike, Yoshinao; Minami, Shohei; et al.
ABSTRACT: Adolescent idiopathic scoliosis (AIS) is a serious health problem affecting 3% of live births all over the world. Many loci associated with AIS have been identified by previous genome wide association studies, but their biological implication remains mostly unclear. In this study, we evaluated the AIS‐associated variants in the 7p22.3 locus by combining in silico, in vitro, and in vivo analyses. rs78148157 was located in an enhancer of UNCX, a homeobox gene and its risk allele upregulated the UNCX expression. A transcription factor, early growth response 1 (EGR1), transactivated the rs78148157‐located enhancer and showed a higher binding affinity for the risk allele of rs78148157. Furthermore, zebrafish larvae with UNCX messenger RNA (mRNA) injection developed body curvature and defective neurogenesis in a dose‐dependent manner. rs78148157 confers the genetic susceptibility to AIS by enhancing the EGR1‐regulated UNCX expression. © 2022 American Society for Bone and Mineral Research (ASBMR).